Cardioprotective Effect of Betulinic Acid on Myocardial Ischemia Reperfusion Injury in Rats - Xia, Anzhou (Hindawi Publishing Corporation, 2014)
Objectives. This study aims to investigate the effect of betulinic acid (BA) on myocardial ischemia reperfusion/injury in an open-chest anesthetized rat model. Methods. The model was induced by 30 minutes left anterior descending occlusion followed by 2 hours reperfusion. There are six groups in our present study: sham operation group, ischemia/reperfusion group, low-dosage BA group, medium-dosage BA group, high-dosage BA group, and fosinopril sodium group. Rats in the latter four groups were administrated with BA (50, 100, and 200 mg/kg, i.g.) or fosinopril sodium (10 mg/kg, i.g.) once a day for 7 days before operation, respectively. Rats in the former two groups were given the same volume of vehicle (0.5% CMC-Na, i.g.). During the operation, cardiac function was continuously monitored. Serum LDH and CK were measured with colorimetric assays. The expression of Bcl-2 and Bax and the apoptosis of cardiomyocytes were investigated with western blot and TUNEL assay, respectively. Results. Pretreatment with BA improved cardiac function and attenuated LDH and CK activities compared with IR group. Further investigation demonstrated that the expression of Bcl-2 and Bax and TUNEL assay was in line with the above results. Conclusion. BA may reduce the release of LDH and CK, prevent cardiomyocytes apoptosis, and eventually alleviate the extent of the myocardial ischemia/reperfusion injury.